(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: Dactylography is the process of comparing two instances of friction ridge skin impressions, from human fingers or toes, or even the palm of the hand or sole of the foot, to determine whether these impressions could have come from the same individual. It is useful in medicolegal case for recognition of suspect, victims, and another person who touches the surface and for the diagnosis of inheritable disease. Fingerprint scans are also used in digital mission of India, biometric systems, validating electronic registration, cashless transactions, library access, and forensic purpose.1,2 ABO blood group system was discovered at University of Vienna by Austrian Scientist Karl Landsteiner. ABO and Rh blood group systems are of major importance compared to other systems.3ABO is further classified into four principal types: A, B, AB, and O. There are two antigens and two antibodies responsible for ABO type. Rh blood group is one of the most complex blood groups in human and it is further classified into Rh-positive and Rh-negative due to the presence of absence of D antigen.4 The frequency of blood group A is greater and the frequency of blood group O less in patient suffering from cancer of the stomach than in general population of the locality in which they live and there is an inherited element in the susceptibility or to protection against cancer of stomach.5 In none of the disease is there any significant difference in sex proportion or in age between patient of the four blood group and there is no indication of any difference in ABO frequencies between gastric and duodenal ulcer.6 Objective:The aim of this study was to find correlation between ABO and Rh blood group with dermatoglyphic pattern in human beings. Results:Out of total 149, the most common pattern of fingerprint was loops 761(51%), followed by whorl 490 (33%), arch 199 (13%) and composite 40 (3%). Wherein 300 were A+ve, 10 A-ve, 540 B+ve, 50 B-ve, 90 AB+ve, 10 AB-ve, 470 O+ve and 20 O-ve. The different patterns of fingerprints were 761 loops, 490 whorl, 199 arch and 40 composite.Conclusion:This study concludes that distribution of pattern of fingerprints is not only related to gender and blood group but it is also related to individual fingers of both hands separately.